Modification of Dynamic Voltage Restorer for Improved Power Quality in Industrial Electrical Networks - Rosyadi, Marwan; Siswanto, Agus (Mestro: Jurnal Teknik Mesin dan Elektro, 2025)
Reliable power quality is a crucial factor in maintaining continuity and operational efficiency in industrial power grids. Power quality disturbances such as voltage sags, voltage swells, and interruptions can cause equipment damage, decreased productivity, and increased operational costs. Dynamic Voltage Restorers (DVRs) have proven effective in addressing voltage disturbances, but conventional devices have limitations, specifically, they are only able to compensate for voltage drops up to approximately 30% of the nominal value and cannot address interruption disturbances. This study proposes a modified DVR with the addition of an energy storage system and an adaptive control algorithm to expand the voltage compensation capabilities, including under extreme voltage sags and interruption disturbances. Simulation results show that the modified DVR is able to maintain load voltages close to the nominal value under various disturbance scenarios, thereby significantly improving the power quality and reliability of the industrial power grid.